Peraturan Daerah Kota Yogyakarta Nomor 8 Tahun 2010 Tentang Peralihan BPHTB Kota Yogyakarta (Studi Periode tahun 2010-2012) - , HANIF HERDUTANTO, Dr. Subando Agus Margono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses the role of the sector in the development of a regional tax . There are several types of local taxes What are today , this is in accordance with the spirit of regional autonomy in Indonesia . Each local government shall be responsible for and manage the potential tax and maximum region well . In this study researchers concentrate on the discussion BPHTB tax , where the tax is a transfer from the center to the regions . So that local governments obtain new additional revenue potential of the tax sector . This thesis would like to see and explain how the mechanism of the transition from the center to the area applied , the tax would be able to increase revenue in the city Yogyakarta. This research aims to determine the factors that affect the implementation apasajakah the policy is applied . So it can be a material consideration in subsequent policies . In this study using qualitative research where the data sources used in the form of the interview along with the data obtained from DPDPK as the implementing agency BPHTB collection in the city of Yogyakarta .